EFFICIENCY OF ISLAMIC BANKS: EVIDENCE FROM ISLAMIC WINDOWS OF CONVENTIONAL BANKS IN ETHIOPIA - Ali, Abdu Seid; Hailu, Suadiq Mehammed (International Journal of Islamic Banking and Finance Research, 2022)
The study examines the cost and technical efficiency of selected Islamic banking windows of conventional banks in Ethiopia during the period of 2016-2020. The parametric method, stochastic frontier approach (SFA) was employed to measure both cost and technical efficiency of the banks. The efficiency scores of the sampled banks can be measured based on their performance in utilizing inputs to successfully generate output during the study period. It gauges the service quality of the banks taking loans and deposits as well as operating income and expenses into consideration. The study uses time series data from four conventional banks which provide Islamic banking widow in Ethiopia. The statistical findings show that the conventional banks have fairly better technical efficiency individually and collectively; however, the cost efficiency scores indicate that the banks are not efficient enough in terms of minimizing costs for a given scale and mix of outputs. Similarly, the results of the stochastic technical frontier estimates uncovers that there is positive significant relationship between the input variables namely total deposits and total operating expenses and output variables namely total financing and total operating income. The outputs remain an essential contributor to the cost efficiency in Islamic windows conventional banks in Ethiopia. JEL Classification Codes: G01, G21, G24.